2012
DOI: 10.3892/etm.2012.724
|View full text |Cite
|
Sign up to set email alerts
|

Association between the levels of polyunsaturated fatty acids and blood lipids in healthy individuals

Abstract: The levels of polyunsaturated fatty acids (PUFAs) in blood is closely associated with the status of the health of individuals; in particular, the lack of ω-3 fatty acids may lead to the development of numerous diseases. The aim of this study was to investigate the levels of PUFAs, and their correlation with triglycerides and other factors in blood. The levels of PUFAs and blood lipids were detected in 156 healthy individuals; the blood samples were tested by combined thin-layer and gas liquid chromatographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…In agreement with an investigation based on 4 male populations (US white, Japanese American and Japanese and Korean), the strongest association was reported with large VLDL [13]. Regarding LDL variables, the non-significant relationship between n-6 PUFAs and LDL-C was also observed in Chinese residents [12] and in whites and Japanese Americans [11], but this association was significant and positive in the Japanese [11] and Italian population [10]. The greatest negative association in the present study was observed between serum n-6 PUFAs and concentrations of small LDL particles.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In agreement with an investigation based on 4 male populations (US white, Japanese American and Japanese and Korean), the strongest association was reported with large VLDL [13]. Regarding LDL variables, the non-significant relationship between n-6 PUFAs and LDL-C was also observed in Chinese residents [12] and in whites and Japanese Americans [11], but this association was significant and positive in the Japanese [11] and Italian population [10]. The greatest negative association in the present study was observed between serum n-6 PUFAs and concentrations of small LDL particles.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, we show that serum n-6 PUFAs are strongly related to a favorable serum lipoprotein subclass profile in terms of cardiovascular risk. The high negative correlation obtained between n-6 PUFAs (relative proportion to total FAs) and total triglyceride concentration in our study (−0.59) was very similar to that observed in an Italian sample (−0.58) [10], and multiple regression models from the post-World War II birth cohort (ERA-JUMP) study including 3 populations (US white, Japanese American and Japanese) of middle aged men also showed an inverse relationship [11]; however, n-6 PUFAs (relative to total PUFAs) were not associated with triglycerides in the Chinese population [12]. Explained by the fact that the majority of triglyceride molecules are carried out in VLDL particles, n-6 PUFAs were strongly correlated with VLDL subclasses.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…(three cis double bond) (30). Polyunsaturated fatty acids omega-3 (PUFA), particular eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), are bioactive lipids that positively impact on signalling pathways involved in the development of cardiovascular diseases, so cardioprotective action of PUFA omega-3 has been approved (31,32). Omega-3 may increase high density lipoprotein cholesterol (HDL), but it may decrease the triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%